Identity-based Signcryption Groupkey Agreement Protocol Using Bilinear Pairing - Reddi, Sivaranjani; Borra, Surekha (Informatica, 2017)
This paper proposes a key agreement protocol with the usage of pairing and Malon-Lee approach in key agreement phase, where users will contribute their key contribution share to other users to compute the common key from all the users key contributions and to use it in encryption and decryption phases. Initially the key agreement is proposed for two users, later it is extended to three users, and finally a generalized key agreement method, which employs the alternate of the signature method and authentication with proven security mechanism, is presented. Finally, the proposed protocol is compared with the against existing protocols with efficiency and security perspective.